Analysis of Pipe Coating Resistance to Internal and External Corrosion: An Experimental Study in the Laboratory PT Bredero Shaw Indonesia - Rudianto; Syahrir; Riswan (LP2M IAIN Palopo, 2025)
This study aims to analyze the resistance of pipe coatings to internal and external corrosion through experimental studies in the laboratory of PT Bredero Shaw Indonesia. Two types of coatings, namely Fusion Bonded Epoxy (FBE) and Polypropylene (PP), were tested through laboratory simulations using the Salt Spray Test Method (ASTM B117), hydrocarbon-based internal corrosion tests, as well as electrochemical impedance (EIS) measurements and adhesion tests (pull-off tests). The research design used a descriptive experimental test approach with analysis of impedance values and adhesion strength. The experimental results showed that PP coatings had higher resistance to external corrosion, while FBE coatings were superior in adhesion strength to internal pressure. Laboratory simulations proved effective in evaluating coating performance under extreme environmental conditions and can be used as a basis for selecting industrial pipe protectors. These findings encourage the importance of using coating systems that are appropriate to the operational characteristics of the pipe.